2017
DOI: 10.1038/sdata.2017.168
|View full text |Cite
|
Sign up to set email alerts
|

Jaw biodynamic data for 24 patients with chronic unilateral temporomandibular disorder

Abstract: This study assessed 24 adult patients, suffering from severe chronic unilateral pain diagnosed as temporomandibular joint (TMJ) disorder (TMD). The full dentate patients had normal occlusion and had never received an occlusal therapy, i.e., were with natural dental evolution/maturation. The following functional and dynamic factors were assessed: (1) chewing function; (2) TMJ remodeling or the condylar path (CP); and (3) lateral jaw motion or lateral guidance (LG). CPs were assessed using conventional axiograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 17 publications
(19 reference statements)
0
9
0
3
Order By: Relevance
“…We had ensured the deglutition function when the subjects worn the compound could not be affected. Multiple previous studies utilized the reliable K7 Evaluation System (Myotronics®) to monitor the jaw motion [ [18] , [19] , [20] ]. This equipment could accurately trace the mandibular trajectory in swallowing pattern.…”
Section: Methodsmentioning
confidence: 99%
“…We had ensured the deglutition function when the subjects worn the compound could not be affected. Multiple previous studies utilized the reliable K7 Evaluation System (Myotronics®) to monitor the jaw motion [ [18] , [19] , [20] ]. This equipment could accurately trace the mandibular trajectory in swallowing pattern.…”
Section: Methodsmentioning
confidence: 99%
“…As a common habit and a possible contributor of TMD, CSP could result into excessive load on the preferred chewing side of TMJ than that on the contralateral side, leading to the anatomic and structural changes of TMJ, including cartilage, 8 glenoid fossa 9 and condyle 10 . In addition, CSP can influence multiple aspects of mastication, like muscle activity, 11 occlusion, 2,12 condylar path and anterior guidance during chewing 6,13 . All these results indicated that CSP might be a potential contributor of TMD.…”
Section: Introductionmentioning
confidence: 93%
“…Some epidemiologic studies have shown that people with CSP have a higher prevalence of temporomandibular disorders (TMD), 3‐5 and also a great majority of TMD patients show CSP. Besides, the preferred chewing side often is the symptomatic side of the joints in TMD patients 6 3,4 and have a strong association with TMD symptoms 7 …”
Section: Introductionmentioning
confidence: 99%
“…Desarrollándose así en algunas pacientes relaciones molares y caninas diferentes en cada lado de la arcada; también se puede observar como consecuencia de una masticación viciosa cambios en la forma y posición de los cóndilos 6 . De hecho, la masticación unilateral entra dentro de las parafunciones, ya que no es normal que las personas usen un solo lado para comer, pero la mayoría de los pacientes son masticadores unilaterales, aunque la masticación puede realizarse de forma bilateral, cerca del 78% de los individuos siente preferencia por un lado en el que se realiza la mayor parte de la masticación 7 . Para los pacientes, masticar bilateral o unilateralmente es lo mismo, para ellos esto no marca ninguna diferencia en su sistema estomatognático esto se debe a que no conocen o conocen muy poco que en un paciente masticador bilateral existe una llamada posición intercuspidea que generalmente representará la posición de contacto funcional armónico, siendo llamada también oclusión céntrica donde normalmente los cóndilos se encuentran estables dentro de la fosa articular con una leve tensión, representando esto un caso normal de oclusión 7 .…”
Section: Introductionunclassified